Elevated temperature effect on tension fatigue behavior and failure mechanism of carbon/epoxy 3D angle-interlock woven composites. (15th July 2021) - Li, Dian-sen; Dang, Ming-guang; Jiang, Lei
Abstract: This paper reported elevated temperature effect on tension fatigue behavior and failure mechanism of carbon/epoxy 3D angle-interlock woven composites. The S-N curve shows that the composite has good fatigue properties, and the fatigue properties decrease to a certain extent at elevated temperature. The tensile fatigue limit of composite is 38% and 30% stress level at 25 °C and 100 °C, respectively. Tensile modulus-fatigue life curve shows that the composite has obvious three-stage cumulative damage development, while the high temperature increases the material's viscoelasticity and toughness. Fracture morphologies indicate that the composite exhibits jagged inclined fracture. The main fatigue failure mechanism is matrix microcracks propagate and expand inside the material along warp and weft direction. The microcracks propagate to the fiber/matrix interface, resulting in stress concentration and debonding of the interface. And the fracture of a large number of warp fibers and fiber bundles eventually causes the composite to fail. At high temperatures, the material softens, the interface bonding strength becomes worse, leading to more serious fiber pullout and breakage, and the brittleness of the material weakens.